Evaluating Natural History and Follow Up Strategies for Non-obstructive Urolithiasis in Pediatric Population - Sheth, Kunj R.; White, Jeffrey T.; Perez-Orozco, Andre F.; Debolske, Natalie D.; Hyde, Christopher R.; Geistkemper, Christine; Roth, David R.; Austin, Paul F.; Gonzales, Edmond T.; Janzen, Nicolette K.; Tu, Duong D.; Mittal, Angela G.; et al. (Frontiers in Pediatrics, 2018)
Objective: While small nonobstructive stones in the adult population are usually observed with minimal follow-up, the same guidelines for management in the pediatric population have not been well studied. We evaluate the clinical outcomes of small non-obstructing kidney stones in the pediatric population to better define the natural history of the disease. Methods: In this IRB-approved retrospective study, patients with a diagnosis of kidney stones from January 2011 to March 2017 were identified using ICD9 and ICD10 codes. Patients with ureteral stones, obstruction or stones greater than 5mm in size were excluded. Patients with no follow-up after initial imaging were also excluded. Patients with a history of stones or prior stone interventions were included in our population. Frequency of follow-up ultrasounds while on observation were noted and any ER visits, stone passage episodes, infections, and surgical interventions were documented. Results: Over the 6-year study period, 106 patients with non-obstructing kidney stones were identified. The average age at diagnosis was 12.5 years and the average stone size was 3.6mm. Average follow-up was 17 months. About half of the patients had spontaneous passage of stones (54/106) at an average time of 13 months after diagnosis. Stone location did not correlate with spontaneous passage rates. Only 6/106 (5.7%) patients required stone surgery with ureteroscopy and/or PCNL at an average time of 12 months after initial diagnosis. The indication for surgery in all 6 cases was pain. 17/106 (16%) patients developed febrile UTIs and a total of 43 ER visits for stone-related issues were noted, but no patients required urgent intervention for an infected obstructing stone. Median interval for follow-up was every 6 months with renal ultrasounds, which then was prolonged to annual follow up in most cases. Conclusions: The observation of pediatric patients with small non-obstructing stones is safe with no episodes of acute obstructive pyelonephritis occurring in these patients. The sole indication for intervention in our patient population was pain, which relates that routine follow-up ultrasounds may not be necessary for the follow-up of pediatric nonobstructive renal stones ≤ 5mm in size.